Celebrations mit children within religious education: Ein Beitrag zu einer subjektorientierten Religionspädagogik (Pedagogical Horizons, 2020)
Religious education without the relevance to life of pupils does not make any sense. Due to this the evangelican theologican Joachim Kunstmann calls for a subject-oriented religious pedagogics that starts with the individual subjects, their experiences and needs, their questions concerning their meaning of life and finally their desires. Religious learning is not possible without the feelings of individual concern and being touched.                   Regarding to the explanations of Joachim Kunstmann this article deals with the question, what kind of celebrations enhances a subject-oriented religious education at primary schools.The item particularly focuses on the performing of birthday celebrations. By using a concrete practical example of my long-lasting experience this kind of celebrations will be reviewed of its pertinence for a subject-oriented religious education.For the progressing of the topic knowlegde of neuroscience and psychology will be included in the religious pedagogical approach of Kunstmann.
Keywords: Subject-oriented religious education, relevance to life, reference to experience, birthday celebrations, spirituality, esteem, esthetic staging.